Comparative study of nasal cavity drug delivery efficiency with different nozzles in a 3D printed model - Fang,Shengjian; Rui,Xiaoqing; Zhang,Yu; Yang,Zhangwei; Wang,Weihua (PeerJ, 2024)
Background Nasal sprays are widely used in treating nasal and sinus diseases; however, there are very few studies on the drug delivery efficiency of nasal sprays. In this study, the drug delivery efficiency of three different nasal spray devices was evaluated in vitro using a 3D printed cast model of nasal cavity. Methods Three nasal spray devices with different nozzles and angles of administration were used in the 3D model of the nasal cavity and paranasal sinuses. The spraying area (SA), maximal spraying distance (MSD), and spraying distribution scores on the nasal septum and lateral nasal wall were recorded. Results Different nasal spray devices have their own characteristics, including volume of each spray, SA, and plume angle. The SA of the three nozzles on the nasal septum increased with an increasing angle of administration. When the angle of administration was 50°, each nozzle reached the maximal SA. There was no statistically significant difference in MSD among the three nozzles at the three angles. The total scores for each nozzle using the three different spraying angles were as follows: nozzle A, 40° > 30° > 50°; nozzle B, 30° > 40° > 50°; and nozzle C, 30° > 40° > 50°. The total scores for different nozzles using the same angle were statistically significantly different and the scores for nozzle C were the highest. Nozzle C had the minimum plume angle. None of the three nozzles could effectively delivered drugs into the middle meatus at any angle in this model. Conclusions The design of the nozzle affects drug delivery efficiency of nasal spray devices. The ideal angle of administration is 50°. The nozzle with smaller plume angle has higher drug delivery efficiency. Current nasal spray devices can easily deliver drugs to most areas of the nasal cavity, such as the turbinate, nasal septum, olfactory fissure, and nasopharynx, but not the middle meatus. These findings are meaningful for nozzle selection and device improvements.
Keywords: 3D model; Nasal administration; Nasal spray; Delivery efficiency; Nozzle